Ethnobotany of Local Foodstuff Plants Used By Bugbug Community In Karangasem, Bali, Indonesia - Dewa Ayu Sri Ratnani; I Ketut Junitha; Eswaryanthi Kusuma Yuni; Desak Nyoman Budiningsih (International Journal of Applied Science and Sustainable Development (IJASSD), 2024)
The aims of this research were (1) Reveal to the diversity of local foodstuff plants utilized by Bugbug community; (2) to analyze traditional knowledge of local foodstuffs plants of Bugbug community; (3) to analyze the Use Value (UV) and Index Cultural Significance (ICS) of local foodstuffs plants. The research was conducted in Bugbug Karangasem, Bali, from January 2021-March 2021. Data were collected using qualitative methods, semi-structured interviews, moderate participation observation, and documentation. Key informants were selected using purposive and snowball sampling to obtain ten key informants and 48 respondents. The use value of plants is calculated by UV, cultural importance with ICS. The level of traditional knowledge was measured by the Phillips and Gentry equations and analyzed by the Kruskal Wallis and Mann Whitney Test. The traditional knowledge of local foodstuff plants was calculated using the Phillips and Gentry equations and analyzed with the Kruskal Wallis and Mann Whitney Test. Traditional knowledge of local foodstuff plants between age groups is different. Meanwhile, knowledge between genders is not different. The diversity of local foodstuff plants in Bugbug Village is 126 species, 47 families, the most families being Musaceae. The high diversity of plants found is caused by specific ecosystems from hilly areas and beaches. The most widely used part of the plant is the fruit. Most plant habitus is an herb. Herbs are easy to grow in various locations and are found in semi-wild status. The highest plant use value and ICS are Arenga pinnata L.